The effect of work-family conflict and work overload on turnover intention with job stress as mediation in state-owned enterprises employees - Budhi Alfiyyah Alyaa; Daud, Ilzar; Hendri, M. Irfani; Kalis, Maria Christiana Iman; Fahruna, Yulyanti (SEAN Institute, 2024)
The main focus of this study is to find the impact of work-family conflict and work overload on turnover intention in SOEs employees, with job stress as a mediator. Data were collected from respondents working in various SOEs at PT PLN, PT TASPEN, PT Telkom Indonesia, PT Pertamina, and PT Pelabuhan Indonesia. The collected data were analyzed using Structural Equation Modeling (SEM) analysis techniques and AMOS software. The results of this study are positive and significant. The variables of work-family conflict, work overload, and jobs tress have a positive influence on turnover intention. The variables of work-family conflict and work overload positively and significantly influence job stress. Results of the mediation analysis reveal that job stress plays a mediating role in the correlation between work-family conflict and work overload, and has an impact on turnover inetntion. This research is expected to help improve employee retention and welfare in the SOEs environment